Use of liquid lithography to form in vitro intestinal crypts with varying microcurvature surrounding the stem cell niche. (26th October 2021) - Howard, R Logan; Wang, Yuli; Allbritton, Nancy L
Abstract: Objective. The role of the crypt microarchitecture and surrounding tissue curvature on intestinal stem/proliferative cell physiology is unknown. The utility of liquid lithography in creating polydimethylsiloxane (PDMS) micropillar stamps with controlled tip curvature was assessed. Using these stamps, the impact of microcurvature at the crypt base on intestinal cell and cytoskeletal behavior was studied. Approach . An SU-8 master mold as a support, polyols of varying surface energies as sacrificial liquids, and liquid PDMS as the solidifiable material were combined using liquid lithography to form PDMS micropillar arrays. Vapor phase deposition of organosilane onto the master mold was used to modify the surface energy of the master mold to shape the micropillar tips. Collagen was molded using the micropillar arrays forming a scaffold for culture of human primary colonic epithelial cells. Cell proliferation and cytoskeletal properties were assessed using fluorescent stains. Main results . Liquid lithography using low surface energy polyols (<55 dynes cm −1 ) generated convex-tipped PDMS micropillars, while polyols with higher surface energies (>55 dynes cm −1 ) yielded concave-tipped PDMS micropillars. Gradients of octyltrichlorosilane deposition across a master mold with an array of microwells yielded a PDMS micropillar array with a range of tip curvatures. Human primary colonic epithelial cells cultured on micropillar-molded collagen scaffolds demonstrated a stem/proliferative cell compartment at the crypt base. Crypts with a convex base demonstrated significantly lower cell proliferation at the crypt base than that of cells in crypts with either flat or concave bases. Crypts with a convex base also displayed higher levels of G-actin activity compared to that of crypts with flat or concave bases. Significance . Liquid lithography enabled creation of arrays of in vitro colonic crypts with programmable curvature. Primary cells at the crypt base sensed and responded to surface curvature by altering their proliferation and cytoskeletal properties.